The effect of forward markets and currency options on international trade - Udo Broll; Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
This paper presents a model of a competitive risk averse exporting firm under exchange rate uncertainty. If forward market contracts are available neither the distribution parameters of the exchange rate nor the degree of the firm's risk aversion have any impact on the export level. But this Separation property does not hold in the case of currency options. It is shown that under some conditions, exports are larger under exchange rate uncertainty in the presence of currency options than they are in the so-called certainty equivalent case, and that exports increase with volatility of the exchange rate provided that risk aversion is not too high.
Keywords: 330